Geographies of Anticolonialism : Political Networks Across and Beyond South India, C. 1900-1930. - Davies, Andrew (RGS-IBG Book Ser., 2019)
A fresh approach to scholarship on the diverse nature of Indian anticolonial processes.-Brings together a varied selection of literature to explore Indian anticolonialism in new ways -Offers a different perspective to geographers seeking to understand political resistance to colonialism -Addresses contemporary studies that argue nationalism was joined by other political processes, such as revolutionary and anarchist ideologies, to shape the Indian independence movement -Includes a focus on a specific anticolonial group, the 'Pondicherry Gang, ' and investigates their significant impact which went beyond South India -Helps readers understand the diverse nature of anticolonialism, which in turn prompts thinking about the various geographies produced through anticolonial activity.